La gramática funcional y el desarrollo de competencias interculturales en la enseñanza del español como lengua extranjera - Fonseca, Clara Inés (Colombian Applied Linguistics Journal, 2014)
The purpose of this document is to describe a discourse analysis, based on functional grammar (FG), as an approach to intercultural competence in the Spanish as a foreign language classroom. This alluded to the complementary relationship between language and culture emphasizing what to say about the “other” and how to say it. FG could provide an “objective” data culture analysis as it has to do with language used on different texts and contexts; so the descriptions of language systems are integrally related with the descriptions of social contexts. As an illustration, we will describe the social actors and the verbal processes on a lyric of “vallenato”, and their contextualization on Colombian Caribbean’s gender relations.